Sports entertainment programs from the perspective of College student audience psychology spread excellent traditional Chinese culture - Ma, Ruixue; Hou, Kun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This research will investigate the diffusion of great traditional Chinese culture through sports entertainment programs from a psychological standpoint. Based on the needs of the study and the actual investigation situation, this article employs the methods of literature, questionnaire, and mathematical statistics to select a total of 800 college students to participate in this survey to determine whether there are significant differences in the participation of college students of different genders and grades in traditional national sports. The survey indicated that college student engagement in traditional national sports is in an unfavorable state. College students pay more attention to traditional national sports, but their understanding is limited, their engagement is limited, and their average participation time is less than thirty minutes. Only when sports entertainment programs have more significant educational impacts from the standpoint of the audience's psychology will sports news be able to disseminate the superb traditional Chinese culture better. This study has significant consequences for the psychology of students.